Medication Compliance for Tuberculosis Patients with Quote TB Light at Public Health Center in 2020 - Ayu Putri Utami; Fajar Ariyanti (Lambung Mangkurat, 2021)
Tuberculosis is a chronic disease that requires prolonged medication and slow recovery, hence the problem that often occurs is the patients’ medication compliance. This study is aimed to identify the Description of the Medication Compliance for Tuberculosis Patients with Quote TB Light in Public Health Center. The method of this study was quantitative descriptive using cross sectional design with 92 patients from February to March 2020. The results showed that 51% of tuberculosis patients had complied with the medication. Based on the dimensions of Quote TB Light, the majority of patients have a good perception regarding: TB services (93.65%); the information received is appropriate (100%); health workers when providing consultations (100%); the availability of infrastructures (66%); the service provided by health workers is appropriate (74.5%); the affordability of TB medication is good (100%); and the attitude of health workers (100%). The conclusion is that the description of the medication compliance of tuberculosis patients based on Quote TB Light is good, but it is necessary to improve the quality of services on health workers’ capability and competence, to make improvements and consistent interventions in waiting time, and to pay attention to the infrastructure in order to provide the comfort for patients.